A Comparison of Group and Individual Incentive Plans - London, Manuel; Oldham, Greg R. (Academy of Management Journal, 1977)
The effects of three variations of group incentive plans on goals and performance were compared in the laboratory and contrasted with individual piece-rate and fixed-rate incentive systems. The results emphasize the importance of both the design of the pay system and the level of a person's performance in the work group.